1994
DOI: 10.1113/expphysiol.1994.sp003740
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and L‐lactate metabolism in pregnant and in lactating ewes fed barley‐ or ground maize‐based diets

Abstract: SUMMARYThe contribution of glucose absorbed from the small intestine to whole-body glucose metabolism was examined in ewes during late pregnancy and early lactation, using diets based on ground barley or ground maize. Glucose and L-lactate turnover in the whole body and the mesenteric-drained viscera were investigated in these ewes using isotope dilution techniques. The net absorption of glucose by the mesenteric-drained viscera and whole-body glucose turnover were unaffected by diet or reproductive status. Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
1
2
1
Order By: Relevance
“…Another potential area that affects the estimations of gluconeogenesis from propionate is its oxidation within the rumen wall. Unlike sheep, where an extensive (60-80%) incorporation of C from propionate to lactate occurs before conversion to glucose (Perry et al, 1994), a negligible (about 3-5%) oxidation of propionate occurs within the rumen epithelium of cows (Bergman, 1990). This is in agreement with the results of Brockman (2005), who indicated that in the movement of C label from glucose to pyruvate or lactate and back to glucose, the exit of the C label was not detected.…”
Section: Discussionsupporting
confidence: 90%
“…Another potential area that affects the estimations of gluconeogenesis from propionate is its oxidation within the rumen wall. Unlike sheep, where an extensive (60-80%) incorporation of C from propionate to lactate occurs before conversion to glucose (Perry et al, 1994), a negligible (about 3-5%) oxidation of propionate occurs within the rumen epithelium of cows (Bergman, 1990). This is in agreement with the results of Brockman (2005), who indicated that in the movement of C label from glucose to pyruvate or lactate and back to glucose, the exit of the C label was not detected.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, Veenhuizen et al [8] fed steers at similar MEI and still reported a 59% increase in glucose turnover following propionate supplementation, at the same level as in this present study (30 mmol·d -1 ·kg BW -1 ). However, the steers presented a lower basal glucose turnover (42 mmol·d -1 ·kg BW -0.75 ) than that measured in the present study (60 mmol·d -1 ·kg BW -0.75 ), or by [14] and [48].…”
Section: Whole Body Glucose Turnover and Propionate Supplementationcontrasting
confidence: 91%
“…In lactating or pregnant ruminants, glucose turnover is clearly affected by changes in glucose requirements [12,[74][75][76]. In adult sheep, glucose turnover was better correlated with energy balance than with intake level, suggesting that the nutritional status of the animal had at least as much influence as the supply of glucose precursors [32].…”
Section: Nutritional Status Of the Animal And Glucose Turnovermentioning
confidence: 99%